2016
DOI: 10.1111/zsc.12174
|View full text |Cite
|
Sign up to set email alerts
|

Budding speciation via peripheral isolation: the Psorodonotus venosus (Orthoptera, Tettigoniidae) species group example

Abstract: Kaya S, C ß ıplak B. (2016). Budding speciation via peripheral isolation: the Psorodonotus venosus (Orthoptera, Tettigoniidae) species group example. --Zoologica Scripta, 45, 521-537. The peripatric or budding species model has remained theoretical until recently. The habitat preference and range pattern of the mountainous Psorodonotus venosus species group, distributed in Anatolia and Caucasus, offered potential to test the predictions of the model. The study aimed to confirm the parameters and to provide evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…The present results confirm previous studies which show ITS1‐5.8S rDNA‐ITS2 nuclear fragments to be uninformative for species‐level phylogenetics of Orthopteran lineages (Kuperus & Chapco, ; Çıplak et al , ; Kaya & Çıplak, ). Although phylogentically uninformative, ITS sequences, on their own or in combination with another marker, can still be used as candidate genes for DNA barcoding, as haplotypes are almost always consistently species‐specific with species delimitation tests.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The present results confirm previous studies which show ITS1‐5.8S rDNA‐ITS2 nuclear fragments to be uninformative for species‐level phylogenetics of Orthopteran lineages (Kuperus & Chapco, ; Çıplak et al , ; Kaya & Çıplak, ). Although phylogentically uninformative, ITS sequences, on their own or in combination with another marker, can still be used as candidate genes for DNA barcoding, as haplotypes are almost always consistently species‐specific with species delimitation tests.…”
Section: Discussionsupporting
confidence: 91%
“…For molecular clock estimates, the COI and 12S–16S matrices were analysed separately using beast v1.8.0 (Drummond et al , ) as previously reported divergence rates for each marker differ considerably (Kaya & Çıplak, ). The nodes of the main clades were dated using a Bayesian coalescence approach, as implemented in beast .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations